New cembrane-type diterpenoids from Bornean soft coral N ephthea sp. with antifungal activity against Lagenidium thermophilum - Kazuka Tani; Takashi Kamada; Phan, Chin Soon; Charles Santhanaraju Vairappan (Taylor & Francis, 2019)
Three new cembrane diterpenes, nephthecrassocolides A-B (1–2) and 6-acetoxy nephthenol acetate (3) along with three known compounds, 6-acetoxy-7,8-epoxy nephthenol acetate (4), epoxy nephthenol acetate (5) and nephthenol (6) were isolated from one population of Nephthea sp. Their structures were elucidated based on spectroscopic data analysis and the antifungal activities of compounds 1–6 were evaluated.